Brazil - Planning for Performance in the Federal Government : Review of Pluriannual Planning, Volume 2. Annexes - World Bank (Washington, DC, 2013)
National development planning is seen as an important tool of economic development, and in Brazil, the 1988 Constitution, includes the "Plano Plurianual de Acao - PPA" (i.e., multi-year development planning), together with the Law of Budget Directives, and the annual budget laws, as part of a set of legal instruments for fiscal, and public expenditure management. Its main role is to provide the government with strategic guidelines for the allocation of public resources, to improve efficiency, and ultimately achieve a higher level of development. To summarize, Brazil's PPA is a unique attempt to use techniques of planning, transform the Brazilian Federal bureaucracy into a modern, results-oriented entity, and effectively provide public goods and services as demanded by its citizens. Its goals of revamping the state's capacity to instill a culture of entrepreneurial management in the public sector, are ambitious; yet, its approach to implementation is advisedly cautious. Its conceptual design is built explicitly on experiences form the previous PPA, and, the development of the new plan followed a careful preparation process that lasted more than two years. The "model" is multi-faceted, and highly complex, appropriate for an evolving process, in which the Government is constantly introducing adjustments to the model's design, as encountered from practical implementation challenges.